Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.apmt.2020.100643
|View full text |Cite
|
Sign up to set email alerts
|

The crucial impact of cerium reduction on photoluminescence

Abstract: Rare earth-based inorganic phosphors are of great interest for solid-state lighting because some of them present very efficient luminescence properties. However, their performances strongly depend on several parameters. For multivalent dopants such as cerium, a widely used activator in the lighting industry, a synthesis in reducing atmosphere is often required to stabilize the dopant in its lower oxidation state. Surprisingly, this crucial step is not much considered, and the presence of the reduced state only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Several groups have performed XPS analysis to characterize samples doped with Ce [17,52] , Eu [24,53,54] , or Mn [30,55] ions. quantification of each valence state of a dopant can be carried out [56][57][58][59][60][61] . In that respect, Avci et al [56] reported the investigation of Eu-doped CaAl 2 O 4 material.…”
Section: Quantification Of the Valence State Of Dopantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several groups have performed XPS analysis to characterize samples doped with Ce [17,52] , Eu [24,53,54] , or Mn [30,55] ions. quantification of each valence state of a dopant can be carried out [56][57][58][59][60][61] . In that respect, Avci et al [56] reported the investigation of Eu-doped CaAl 2 O 4 material.…”
Section: Quantification Of the Valence State Of Dopantsmentioning
confidence: 99%
“…While EXAFS (Extended X‐ray Absorption Fine Structure) provides information on atom environment (bond lengths, neighboring element, …), the X‐ray Absorption Near Edge Spectroscopy (XANES) region is related to local atomic states. Thus, the identification and precise quantification of each valence state of a dopant can be carried out [56–61] . In that respect, Avci et al [56] .…”
Section: Quantification Of the Oxidation States Of Dopantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare-earth-based optical materials with a large Stokes shift, high color purity, and strong luminescence properties have been widely used in optical devices, communication, sensing, and bioimaging. Among them, lanthanide metal–organic frameworks (Ln-MOFs) have attracted great interest in the field of chemical sensing due to the tailorable luminescence properties and diverse energy-transfer processes derived from their editable components (organic ligands and metal ions/clusters). Fluorescent signal changes in the sensing process gave high sensitivity and visualization to Ln-MOFs. Up to now, Ln-MOFs have been used to detect heavy-metal ions or anions, nitroaromatic explosives, volatile organic compounds (VOCs), biomarkers, etc. Shi’s group synthesized the novel {[Eu 2 (L) 3 (DMF) 2 ]·DMF·MeOH} n (Ln-MOF 1 ; H 2 L = 5-(4 H -1,2,4-triazol-4-yl)­benzene-1,3-dicarboxylic acid, DMF = N , N -dimethylformamide, and MeOH = methanol), which shows the red luminescence characteristic of Eu III . There is a competitive absorption between polychlorinated benzenes and Ln-MOF 1 , which prevents the “antenna effect”.…”
Section: Introductionmentioning
confidence: 99%
“…This HT approach uses the ability of several dopants such as Mn or Eu to exhibit different emissions according to their oxidation states. [19,[23][24][25][26] The strategy consists in firstly synthesizing a few materials codoped with different amounts of two dopants. Then, an oxidation step under a gradient of temperature is carried out to tune the oxidation states of dopants and the resulting emissions.…”
Section: Introductionmentioning
confidence: 99%